Revealing the Critical Factors for Tax Compliance Behaviour: An Application of Importance-Performance Map Analysis - Faustine Juma Masunga (TIJAB (The International Journal of Applied Business), 2025)
Background: Scholars have devoted more time to the concept of tax compliance behaviour in recent years. Insufficient tax revenue collection is one effect of low tax compliance behaviour. The problem of low tax compliance behaviour is universal. If not addressed, emerging and fastest-growing economies with vastly commanding tax authorities will have insufficient tax revenue to finance their budgets. Objective: This study sought to divulge the critical factors for tax compliance behaviour. Transforming the ways of tax collection into a digital era is central to easy tax compliance. To meet this objective, this study linked the electronic tax system employing the Importance Performance Map Matrix (IPMM), a crucial matrix to determine the importance and performance of the constructs to explain tax compliance behaviour. Method: This study adopted the survey method. Information on variables under investigation was collected from business centres. A stratified random sampling was employed to obtain the taxpayers who use the e-tax system. The study analyzed data using Structural Equation Modelling (SEM) using SmartPLS3. Results: Unveiled that behavioural intention is a critical factor in enhancing the behaviour of taxpayers to comply. Additionally, performance expectancy highly influences taxpayers to comply. When taxpayers have high expectations of productivity and return on the e-tax system they use, it drives more intention to voluntary tax compliance. Conclusion: Tax authorities are argued to introduce or design e-tax systems that improve taxpayers’ businesses and increase government tax revenue. Keywords: Behavioural Intention; Tax Compliance Behaviour; Importance Performance Map Matrix.